Transcriptome sequencing reveals a lncRNA-mRNA interaction network in extramammary Paget's disease - Da-chao Zheng; Yan-ting Shen; Zi-wei Wei; Xiang Wan; Min-kai Xie; Hai-jun Yao; Zhong Wang (BMC, 2021)
Abstract Background Extramammary Paget's disease (EMPD) is a rare malignant intraepidermal adenocarcinoma that is poorly understood. Regulatory long noncoding RNAs (lncRNAs) are characterized in many species and shown to be involved in processes such as development and pathologies, revealing a new layer of regulation in different diseases, especially in cancer studies. In the present study, we used high-throughput sequencing to reveal the lncRNA-mRNA interaction network in extramammary Paget's disease. Methods High-throughput sequencing was used to identify differentially expressed lncRNA and mRNA profiles between EMPD patients and healthy controls. Then, a series of bioinformatics analyses were conducted to construct the lncRNA-mRNA interaction network, which was finally confirmed in vitro. Results Six pairs of EMPD tumor and normal skin samples were collected and sequenced to identify the differentially expressed lncRNA and mRNA profiles between EMPD and healthy controls. A total of 997 differentially expressed mRNAs and 785 differentially expressed lncRNAs were identified. The GO and KEGG analyses show that epidermal development and cell adhesion play important roles in EMPD. The results of the lncRNA-mRNA interaction network analysis suggested that NEAT1, PGAP1, FKBP5 and CDON were the pivotal nodes of the network and that lncRNA NEAT1 might regulate mRNA PGAP1, FKBP5 and CDON. The results of the quantitative real-time RT-PCR performed in ten other patients for NEAT1, PGAP1, FKBP5 and CDON were consistent with those of the sequencing analysis. Moreover, an in vitro experiment confirmed the interactions between NEAT1 and PGAP1, FKBP5 and CDON in human immortalized keratinocytes. Conclusion These findings suggest that the lncRNA-mRNA interaction network based on four pivotal nodes, NEAT1, PGAP1 FKBP5 and CDON, may play an important role in EMPD, which will contribute to a deeper understanding of the pathogenesis of EMPD.